(untitled) (SAARC Journal of Agriculture, 2022)
Assessment of genetic diversity among different is a prerequisite for plant breeders in choosing potential parental lines. Ten genotypes of summer growing chilli including one released variety viz., BARI morich-2; one advanced line viz., SRC- 517 and eight local cultivars viz., IAH-160, IAH-164, AHM-206, AHM-217, AC-63, AC-312, RAI-67, and RI-1(6) were characterized with a view to explore genetic diversity within these genotypes based molecular markers. Using eight microsatellite (SSR) primers across 10 genotypes, a total of 30 alleles with an average number of 3.75 alleles per locus were found. The number of alleles detected varied form three (CAMS-864, CAMS-880, CAMS-885) to five (CAMS-647). The allele size ranged from 160 (CAMS-075) to 289 bp (CAMS-864). All most all sets of primers showed high polymorphism (PIC value ≥0.6) except CAMS-880 and CAMS-885 which suggesting the greater genetic diversity in the genotypes. Gene diversity ranged from 0.460 (CAMS-885) to 0.740 (CAMS-647) and the highest and lowest value of Shannon’s Information Index was registered in the same locus with their average value of 1.174. Higher level of genetic differentiation (0.971) and lower level of gene flow value (0.007) which were indicative of the presence of diversity among the genotypes. The genotypes had distinct status in the dendrogram, because of variation in genetic distance values differed from 0.138 to 0.938. SAARC J. Agric., 20(2): 69-82 (2022)